2010
DOI: 10.1053/j.gastro.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor and Interferon-γ Down-regulate Klotho in Mice With Colitis

Abstract: Background & Aims Klotho deficiency in hypomorphic KL mice leads to premature senescence and phenotype consistent with impaired mineral homeostasis. Klotho has anti-inflammatory properties protecting from NO-induced endothelial dysfunction, reduces the expression of endothelial adhesion molecules, and may contribute to T-cell dysfunction. Since defective Ca2+/Pi homeostasis leading to osteopenia/osteoporosis is frequently associated with human IBD, we investigated the changes in Klotho gene expression as a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
90
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 40 publications
7
90
1
3
Order By: Relevance
“…We demonstrated that the protein expression and release level of Klotho were significantly decreased in MH-S cells treated with CSE in a time-and concentration-dependent manner. This notion is consistent with a previous study; Klotho is down-regulated by inflammatory cytokines such as TWEAK or TNF-␣ that decreased klotho gene transcription in renal tubular cells (22,23). Klotho is an important protein involved in the regulation of proinflammatory cytokine release, stress resistance, metabolism, senescence, and aging (24 -27), all of which are linked to the pathogenesis of COPD (5,6,13,29,38).…”
Section: Discussionsupporting
confidence: 80%
“…We demonstrated that the protein expression and release level of Klotho were significantly decreased in MH-S cells treated with CSE in a time-and concentration-dependent manner. This notion is consistent with a previous study; Klotho is down-regulated by inflammatory cytokines such as TWEAK or TNF-␣ that decreased klotho gene transcription in renal tubular cells (22,23). Klotho is an important protein involved in the regulation of proinflammatory cytokine release, stress resistance, metabolism, senescence, and aging (24 -27), all of which are linked to the pathogenesis of COPD (5,6,13,29,38).…”
Section: Discussionsupporting
confidence: 80%
“…In addition Sugiura et al (2005) reported that the renal klotho mRNA and protein expressions were significantly reduced in the rats with renal failure assessed by real-time PCR or western blotting. These results came in accordance with the recorded data of Hu et al (2010) and Thurston et al (2010) were found that klotho down-regulation occurs before changes in other markers of kidney damage. It takes place only 3 h post-ARF may be due to activation and induction of nitric oxide production.…”
Section: Discussionsupporting
confidence: 81%
“…In this regard, systemic delivery of TWEAK (TNF-like weak inducer of apoptosis) or angiotensin II decreases levels of kidney Klotho, and targeting of TWEAK, TNF, or the renin-angiotensin system prevents kidney Klotho downregulation in animal models of kidney injury or systemic inflammation. 3,8,9 Similar functional studies should define the relative in vivo contribution of TGF-b1 to the regulation of kidney Klotho levels. Currently available data support a model where multiple tubular cell stressors decrease Klotho synthesis.…”
mentioning
confidence: 99%
“…For some study participants, the reduction in GFR was rather modest. The inclusion criteria required the estimated GFR (eGFR) using the Chronic Kidney Disease Epidemiology Collaboration study equation 9 to be ,90 ml/min per 1.73 m 2 . Other inclusion criteria were that the patient was not receiving chronic renal replacement treatment at the time of the physical performance assessment, did not have a stroke, was not using a wheel chair, and had completed at least one physical performance measurement.…”
mentioning
confidence: 99%